Budaya Organisasi: Pembentukan Karakter Peserta Didik Di SMPS IT Al-Hijrah - Yuni Syafriani; Fella Annisa Harahap; Suci Ramadhani; Hasbih Sholeh Suryadi; Lucky Tirta (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Education is a process of cultural transformation from one generation to another, the process of forming personality, the process of forming students into good citizens, and preparing the workforce so that the output of education can live properly in society. However, what has happened so far is not supposed to be, the practice of education so far is still oriented towards the process of pursuing and gathering scientific information as much as possible, but forgetting the fundamental aspect of education, namely how to give birth to a generation that is able to live life and life completely relying on Divine values.